A STUDY OF RADIOACTIVE CONTAMINATION OF MARINE BIOTA AFTER THE FUKUSHIMA ACCIDENT - V. P. Ramzaev (Radiacionnaâ Gigiena, 2015)
134Cs and 137Cs contents have been studied in 44 samples of the marine biota including four species of brown and red algae (11 samples), four species of invertebrates (8 samples) and ten species of fish (25 samples). The samples have been collected in the Northwest Pacific Ocean and in the Seas of Okhotsk and Japan within the framework of the Russian monitoring program that started in 2011 to study environmental consequences of the accident at “Fukushima-1” NPP. In 2011–2012, total activity of both cesium radioisotopes for all the samples analyzed did not exceed 1 Bq kg–1 (wet weight). This value is negligible compared to the safe level of 130 Bq kg–1 (for 137Cs) for the fish consumption in Russia. 134Cs, a marker of the Fukushima-derived contamination, has been determined at a level of 0.2–0.4 Bq kg–1 (wet weight) for three samples of pacific saury (Cololabis saira) collected from areas near Shikotan Island in Sempember 2011 and 2012. The study shows that the Fukushima accident has no considerable impact on radiation conditions in the Kuril-Kamchatka region of the Northwest Pacific Ocean and in the Russian waters of the Sea of Japan.